The association between physical activity and depression among weekend catch-up sleepers: results from NHANES 2021–2023 - Kunyu Qiu; Yilei Liu; Yan Zhang; Jie Gu; Yanyan Huang (BMC Psychiatry)
Abstract Background Depression is a prevalent disorder with significant health impacts. Physical activity is known to protect against depression, but its effects may vary in populations with disrupted sleep patterns, such as weekend catch-up sleepers, which refers to participants who sleep longer on weekends than on weekdays. This study examines the dose-response relationship between physical activity and depression in this population. Methods Data from 1,906 participants in the National Health and Nutrition Examination Survey (2021–2023) were analyzed. Physical activity was measured in MET-minutes per week, and depression was assessed using the PHQ-9. Multivariate linear regression, restricted cubic spline, and two-part linear regression models were employed. Results In the adjusted model, physical activity showed a negative trend with depression, though this association did not reach statistical significance in the fully adjusted model. Stratified analyses revealed stronger associations in women (OR = 0.86, 95% CI: 0.75, 0.99, P = 0.0329) and individuals aged 40–60 years (OR = 0.79, 95% CI: 0.65, 0.97, P = 0.0237). A threshold effect was observed, with physical activity below 2.48 MET-min/1000-wk showing a negative association with depression (OR = 0.69, 95% CI: 0.56, 0.85, P = 0.0006). Beyond this threshold, the relationship changed. Conclusion A nonlinear relationship between physical activity and depression was identified in weekend catch-up sleepers, with moderate activity levels (2.48 MET-min/1000-wk) offering the greatest mental health benefits, particularly in women and individuals aged 40–60 years. Clinical trial number Not applicable. Graphical Abstract